Convertible Securities and Earnings Per Share: A Competitive Ranking Algorithm. - Kilpatrick, Bob; Putnam, Karl; Schneider, Harold (The Accounting Review, 1985)
ABSTRACT: This note explains a modified shortcut approach for computing earnings per share when convertible securities are present. In many cases, it can decrease the number of calculations involved when compared to a widely used shortcut procedure.